A Conceptual-Theoretical-Empirical Structure for the Study of Alzheimer Informal Caregivers and Home Health Care Nursing Services. Issue 4 (November 2019) - Garvey, Joanne M.; Dalton, Joanne Marie; Magny-Normilus, Cherlie
The purpose of this article is to describe the process used to create a conceptual-theoretical-empirical structure for a proposed study of policies for home health care nursing services for informal caregivers of persons with Alzheimer disease. The process consisted of linkage of the Conceptual Model of Nursing and Health Policy with Roy's Adaptation Model to guide derivation of a middle-range theory of home health care nursing services for Alzheimer disease informal caregiving, and selection of appropriate empirical research methods.